Lifestyle Behaviors and Suicide-Related Behaviors in Adolescents: Cross-Sectional Study Using the 2019 YRBS Data - Li, Xiaozhi; Chi, Guijun; Taylor, Alyx; Chen, Si-Tong; Memon, Aamir R.; Zhang, Yanjie; Song, Yagang; Li, Jinming; Luo, Xun; Zou, Liye (Frontiers in Public Health, 2021)
Objective: The purpose of this research was to investigate the prevalence of lifestyle behaviours and suicidal outcomes and the association between them using a nationally representative sample of adolescents from the USA. Methods: 13,677 high school students aged 14-18 years were included in this cross-sectional study. The research data were retrieved from the Youth Risk Behavior Surveillance System Survey in 2019. All collected variables on age, sex, grade, race, physical activity, television time, fruit intake, and suicided related outcomes were self-reported by students. Logistic regression models were adopted to examine the association between lifestyle behaviours and the suicidal outcomes. Results: Students who played video/computer games for ≥2 hours had high risk of suicide attempt (OR = 1.55, 95%CI: 1.30-1.85). Daily sleep duration of ≤8 hours was positively associated with considering a suicide attempt (OR = 1.99, 95%CI: 1.62-2.43). In addition, participants who did not engage in any sport team were more likely to report considering a suicide attempt (OR = 1.50, 95%CI: 1.24-1.81). Conclusion: This research suggests that some lifestyle behaviours (e.g., time for video or computer sue, sleep duration, sport team participation, regular breakfast intake, and substance use) are associated with increased risk of suicidal behavior and ideation in high school students. To identify the specific effect of multiple lifestyle factors in influencing the risk of suicidal outcomes in high school students, longitudinal study is warranted in future.